Development of dehydrated candied mango (Mangifera indica Linn) - Saw, Teresita S.; Gatchalian, Miflora M. (1973.)
Dehydrated candied mango was developed using the method of candying and then air drying sliced rare-ripe mango pulp. Variables studied were levels of syrup concentration(40°, 50°, 60°B) and treatment after the plumping process. Treatment involved control(no treatment), dipping in 2% pectin before cabinet drying and soaking in confectioner's sugar after dehydration. Both objective and subjective evaluations were made to determine the effects of the variables on the quality characteristics of the finished product. Results of sensory evaluation indicated that the two best dehydrated candied mangoes were those soaked in 60°B syrup until plum then either dipped in 2% pectin before drying(P9) or soaked in confectioner's sugar overnight after dehydration(P8). Characteristics of the products were: yellow to yellow orange in color, firm but not crisp texture, slight to just recognizable mango odor and slight to characteristic mango flavor. It was rated "like moderately" to "like very much" in acceptability.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango, Candied